Exploring the Impact of Digital Game-Based Learning on STEM Education a Comprehensive Review - Fei, Haoyang (Transactions on Social Science, Education and Humanities Research, 2024)
Digital game-based learning (DGBL) has emerged as a promising approach to enhancing STEM (Science, Technology, Engineering, and Mathematics) education, drawing widespread attention in fields such as education, healthcare, wellness, and hazard prevention. However, discussions on the application of DGBL in STEM education remain insufficiently explored, with existing research largely focused on language learning and lower-grade subjects. Therefore, this study aims to systematically investigate the impact of DGBL on STEM learning outcomes. Researchers conducted a comprehensive search in the Web of Science database, considering factors such as experimental design, sample size, and comparability of study results. Through literature screening and analysis, 19 relevant studies meeting the inclusion criteria were identified. The findings from the included literature reveal that DGBL has a positive impact on STEM learning, encompassing various aspects such as increased learning motivation, improved academic performance, enhanced self-efficacy, and a positive learning experience. As an educational method, DGBL demonstrates significant potential in the STEM field. However, challenges remain, such as the effectiveness of game design, the selection of assessment tools, and the measurement of learning outcomes. Overall, DGBL positively influences STEM learning, and future research should focus on innovative game design, establishing evaluation standards, and more educational practice to further explore the potential of DGBL in STEM learning.